Oxidative desulfurization of commercial diesel catalyzed by tert-butyl hydroperoxide polymolybdate on alumina: optimization by Box-Behnken design - Wan Abdullah, Wan Nazwanie (Springer Verlag, 2015)
In this paper, the performance of oxidative desulfurization of commercial diesel by alumina-supported polymolybdate-based catalyst system was studied. The oxidizing reagent used was tert-butyl hydroperoxide. The catalyst was prepared using wet impregnation method and characterized by FESEM-EDX and X-ray photoelectron spectroscopy. The effects of dopants, catalyst loading, dopant loading, and calcination temperature of the catalyst were investigated. Further investigations on doped molybdenum revealed that Fe-MoO3/Al2O3 catalyst calcined at 500 °C with 10 % of Fe loading and 9 g/L, the catalyst was able to reduce the sulfur in commercial diesel from 440 to 88 ppmw. Response surface methodology involving Box-Behnken was employed to evaluate and optimize Fe-MoO3/Al2O3 preparation parameters (calcinations temperature, catalyst loading, and Fe loading) and their optimum values were found to be 550 °C, 10 g/L and 10 % of calcination temperature, catalyst loading, and Fe loading.